2016
DOI: 10.1097/id.0000000000000451
|View full text |Cite
|
Sign up to set email alerts
|

Iliac Crest Fresh-Frozen Allografts Versus Autografts in Oral Pre-Prosthetic Bone Reconstructive Surgery

Abstract: FFB cannot be considered as successful and safe in alveolar bone reconstruction as autogenous bone grafting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 27 publications
0
37
0
Order By: Relevance
“…Biologic complications including soft tissue dehiscence, graft exposure, partial and total graft loss have been reported in a systematic review after HARA with autogenous bone block [59]. Moreover, temporary and permanent paraesthesia as well as gait disturbances have been described after harvesting autogenous bone graft in conjunction with HARA [47,62,66]. No biologic or technical complications were reported in the comparative study of the present systematic review [29].…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…Biologic complications including soft tissue dehiscence, graft exposure, partial and total graft loss have been reported in a systematic review after HARA with autogenous bone block [59]. Moreover, temporary and permanent paraesthesia as well as gait disturbances have been described after harvesting autogenous bone graft in conjunction with HARA [47,62,66]. No biologic or technical complications were reported in the comparative study of the present systematic review [29].…”
Section: Discussionmentioning
confidence: 58%
“…No biologic or technical complications were reported in the comparative study of the present systematic review [29]. However, a previous published study assessing HARA with allogeneic bone block reported dehiscence and graft exposure as well as partial and total loss of graft before and after implant placement compared with no complications after HARA with autogenous bone block [62]. Likewise, graft exposure and loss have been described after HARA with allogeneic bone block compared with no biologic complications with autogenous bone block [67].…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations